Specifics of COVID-19 in pregnant women and their children - a review - Stanicki, Paweł; Szarpak, Julita; Wieteska, Małgorzata; Kaczyńska, Agnieszka; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: The first cases of SARS-CoV-2 infection were recorded in the last months of 2019 in the Chinese city Wuhan. Since then, COVID-19 has spread throughout the world. Still little is known about the perinatal aspects of COVID-19. Objective of this article is to present the course of coronavirus disease in pregnant women with particular emphasis on the occurrence of intrauterine infection and preterm births. Brief description of the state of knowledge: SARS-CoV-2 calling COVID-19 probably comes from bats sold at the Wuhan market. This virus is highly contagious, it spreads from person to person. The most common symptoms of infection include: fever, cough and ground-glass opacity (GGO) in chest radiographs. The analyzes carried out so far show that the course of the disease in pregnant women is similar to that of non-pregnant patients. Women present typical signs of infection. Most researchers also exclude the presence of intrauterine infection, although there have been reports of isolated cases. The percentage of premature births in women with COVID-19 is higher than average. Summary: The course of coronavirus disease in pregnant women is similar to that of other infected women. While most studies do exclude the presence of a vertical infection, there are reports of severe course of the disease and possible vertical infection. Patients with COVID-19 may be more prone to premature delivery, however, to confirm this thesis, it is necessary to examine a larger number of pregnant women.